A descriptive study of work aggravated asthma. Issue 6 (18th May 2004) - Goe, S K; Henneberger, P K; Reilly, M J; Rosenman, K D; Schill, D P; Valiante, D; Flattery, J; Harrison, R; Reinisch, F; Tumpowsky, C; Filios, M S
Abstract : Background and Aims: Work related asthma (WRA) is one of the most frequently reported occupational lung diseases in a number of industrialised countries. A better understanding of work aggravated asthma (WAA), as well as work related new onset asthma (NOA), is needed to aid in prevention efforts. Methods: WAA and NOA in the United States were compared using cases reported to the National Institute for Occupational Safety and Health (NIOSH) from four state Sentinel Event Notification Systems for Occupational Risks (SENSOR) surveillance programmes for 1993–95. Results: A total of 210 WAA cases and 891 NOA cases were reported. WAA cases reported mineral and inorganic dusts as the most common exposure agent, as opposed to NOA cases, in which diisocyanates were reported most frequently. A similar percentage of WAA and NOA cases still experienced breathing problems at the time of the interview or had visited a hospital or emergency room for work related breathing problems. NOA cases were twice as likely to have applied for workers' compensation compared with WAA cases. However, among those who had applied for worker compensation, approximately three-fourths of both WAA and NOA cases had received awards. The services and manufacturing industrial categories together accounted for the majority of both WAA (62%) and NOA (75%) cases. The risk of WAA, measured by average annual rate, was clearly the highest in the public administration (14.2 cases/10 5 ) industrial category, while the risk of NOA was increased in both the manufacturing (3.2 cases/10 5 ) and public administration (2.9 cases/10 5 ) categories. Conclusions: WAA cases reported many of the same adverse consequences as NOA cases. Certain industries were identified as potential targets for prevention efforts based on either the number of cases or the risk of WAA and NOA.